Optimization of preparation methods for high loading content and high encapsulation efficiency of BSH into liposomes. (March 2021) - Shirakawa, Makoto; Nakai, Kei; Sato, Yuhki; Nakamura, Shunji; Harada, Mari; Ishihara, Kazuki; Yoshida, Fumiyo; Matsumura, Akira; Tomida, Hisao
Abstract: To optimize the preparation methods for liposomes encapsulating mercaptoundecahydrododecaborate (BSH), we examined BSH and lipid concentrations that increased the boron content in liposomes. We improved the BSH encapsulation efficiency and boron content of the liposomes from 4.2 to 45.9 % and 9.5–54.3 μg, respectively, by changing the lipid concentration from 10 to 150 mg/mL. Notably, the boron content increased significantly from 26.2 μg to 326.3 μg at a constant lipid concentration of 30 mg/mL with increased BSH concentrations. Highlights: Preparation methods of liposomes encapsulating BSH were optimized. Various encapsulation methods and concentrations of BSH and lipid were examined. Liposomes prepared by this method encapsulated a high amount of boron. The liposomes have extremely high stability in vitro.